The Ethics of Belief in Paranormal Phenomena - Irwin, Harvey J.; Dagnall, Neil; Drinkwater, Kenneth Graham (Journal of Anomalous Experience and Cognition, 2022)
The philosophical school of Evidentialism holds that people should form, amend, and relinquish a belief wholly in accordance with the available evidence for that belief. This paper reviews the extent to which believers in paranormal phenomena respect Evidentialism’s so-called “ethics of belief.” The analysis focuses on several common violations of evidentialist principles, namely, those pertaining to belief formation as a moral issue, belief inflexibility, belief inconsistency, confirmation bias, and disconfirmation effects. Despite some gaps and methodological shortcomings in the available data, the empirical literature documents an association between paranormal beliefs and a broad lack of sympathy with evidentialist ethics, although the effect sizes of these relations typically are small. The possible basis of this characteristic is briefly explored.